ORR Activity and Stability of Co-N/C Catalysts Based on Silicon Carbide Derived Carbon and the Impact of Loading in Acidic Media. Issue 14 (2nd November 2018) - Teppor, P.; Jäger, R.; Härk, E.; Tallo, I.; Joost, U.; Kook, M.; Paiste, P.; Šmits, K.; Kirsimäe, K.; Lust, E.
Abstract : A simple and facile synthesis method was used to produce two Co-N/C type oxygen reduction reaction (ORR) catalysts. The materials were initially characterized by utilizing a variety of physical methods. Most importantly, the XPS analysis revealed high amounts of pyridinic nitrogen and Co-Nx species in the case of both studied Co-N/C catalysts. The electrochemical characterization showed that both of the synthesized Co-N/C catalysts have a high ORR activity in acidic media, displaying a half-wave potential of 0.70 V vs RHE. Additionally, the effect of varying the catalyst loading was studied and it was found that increasing the catalyst loading from 0.1 to 1.8 mg cm −2 significantly improved the ORR activity and the electron transfer number. Finally, several catalysts were subjected to a week-long stability test in order to establish their activity degradation rates. It was found that increased degradation rates of the Co-N/C catalysts were established at decreased catalyst loadings.